2003
DOI: 10.1354/vp.40-6-677
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Patterns of Nephropathy in Naturally Acquired Canine Visceral Leishmaniasis

Abstract: Abstract. Although the nephropathy of visceral leishmaniasis (VL) is known both in humans and dogs, histopathologic alterations have not been thoroughly studied. We examined renal alterations in 55 dogs with naturally acquired VL compared with five noninfected dogs from an endemic area in northeastern Brazil. Glomerulonephritis was found in 55 dogs, interstitial alterations in 53 dogs, and tubular changes in 43 dogs with VL. The glomerular alterations found were minor glomerular abnormalities (n ϭ 8, 14.5%), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
126
1
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(155 citation statements)
references
References 19 publications
12
126
1
16
Order By: Relevance
“…Differently from the IgG reactions that were weaker in the renal glomeruli, the presence of mesangial cells with fluorescent staining in the cytoplasm was more frequent, and the inflammatory infiltrate was frequently stained in these kidney sections. As to the localization of granules, reaction intensity, and pattern of distribution, the results corroborate those found in renal immunohistochemical assay of 26 dogs with naturally acquired Leishmania chagasi infection (Costa et al, 2003).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Differently from the IgG reactions that were weaker in the renal glomeruli, the presence of mesangial cells with fluorescent staining in the cytoplasm was more frequent, and the inflammatory infiltrate was frequently stained in these kidney sections. As to the localization of granules, reaction intensity, and pattern of distribution, the results corroborate those found in renal immunohistochemical assay of 26 dogs with naturally acquired Leishmania chagasi infection (Costa et al, 2003).…”
Section: Discussionsupporting
confidence: 79%
“…The immunoglobulin deposits were granular and were located on the glomerular capillary walls more than in the mesangium, for IgG as well as for IgM. The distribution of these in the glomerulus was irregular, sometimes focal or diffuse, sometimes global or focal segmental (Costa et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…We detected CD4 + T cells in the glomeruli of five dogs with naturally acquired visceral leishmaniasis from an area where the disease is endemic 17 . Furthermore, in a parallel study we identified glomerulonephritis in 55 dogs naturally infected with visceral leishmaniasis, characterized their glomerular alterations histopathologically, and classified them into six different patterns (proliferative patterns were most common) 16 . Both studies strongly suggested that the migration and proliferation of cells, including T cells, plays a role in the pathogenesis of glomerulonephritis in visceral leishmaniasis.…”
Section: Immunopathogeny In Non-lymphoid Organsmentioning
confidence: 99%
“…Dogs and hamsters with visceral leishmaniasis presenting lesions similar to those in humans are used as models to understand human pathology 16,57 . Until recently, studies of glomerular alterations in visceral leishmaniasis pathogenesis have only found immune complex deposition 19,53,58 .…”
mentioning
confidence: 99%
“…A deposição de imunocomplexos nos glomérulos é o principal mecanismo desencadeador, que pode ocorrer em cães com doenças auto-imunes (como lúpus eritematoso sistêmico), em infecções persistentes (como nos casos de piometra, leishmaniose e diroϐilariose) ou em cães com neoplasmas (Costa et al 2003, Maxie & Newman 2007, Serakides 2010. Cães adultos e idosos podem apresentar deposição de imunocomplexos nos glomérulos, sem, no entanto apresentar sinais de doença renal (Rouse & Lewis 1975).…”
Section: Discussionunclassified